Effects of Extended-Release Nicotinic Acid on Apolipoprotein (a) Kinetics in Hypertriglyceridemic Patients. Issue 9 (September 2015) - Croyal, Mikaël; Ouguerram, Khadija; Passard, Maxime; Ferchaud-Roucher, Véronique; Chétiveaux, Maud; Billon-Crossouard, Stéphanie; de Gouville, Anne-Charlotte; Lambert, Gilles; Krempf, Michel; Nobécourt, Estelle
Abstract : Objective—: To determine the mechanisms by which extended-release nicotinic acid reduces circulating lipoprotein (a) concentrations in hypertriglyceridemic patients. Approach and Results—: Eight nondiabetic, obese male subjects (aged 48±12 years; body mass index, 31.2±1.8 kg/m 2 ) with hypertriglyceridemia (triglycerides, 226±78 mg/dL) were enrolled in an 8 week, double blind, placebo-controlled cross-over study. At the end of each treatment phase, fasted subjects received a 10 µmol/L per kg bolus injection of [5, 5, 5- 2 H3 ]-L-Leucine immediately followed by constant infusion of [5, 5, 5- 2 H3 ]-L-Leucine (10 µmol L −1 kg −1 h −1 ) for 14 hours, and blood samples were collected. A liquid chromatography–tandem mass spectrometry method was used to study apolipoprotein (a) (Apo(a)) kinetics. The fractional catabolic rate of Apo(a) was calculated with a single compartmental model using the apolipoprotein B100 (ApoB100) containing very low density lipoprotein tracer enrichment as a precursor pool. Extended-release nicotinic acid decreased plasma triglycerides (−46%; P =0.023), raised high-density lipoprotein cholesterol (+20%; P =0.008), and decreased Apo(a) plasma concentrations (−20%; P =0.008). Extended-release nicotinic acid also decreased ApoB100 (22%; P =0.008) and proprotein convertase subtilisin/kexin type 9 (PCSK9, −29%; P =0.008) plasma concentrations. Apo(a) fractional catabolic rate and production rates were decreased by 37% (0.58±0.28 versus 0.36±0.19 pool/d; P =0.008) and 50% (1.4±0.8 versus 0.7±0.4 nmol/kg per day; P =0.008), respectively. Conclusions—: Extended-release nicotinic acid treatment decreased Apo(a) plasma concentrations by 20%, production rates by 50%, and catabolism by 37%. ApoB100 and PCSK9 concentrations were also decreased by treatment, but no correlation was found with Apo(a) kinetic parameters. Abstract : Supplemental Digital Content is available in the text.